An L-strip fed stacked patch antenna for maritime satellite communications - 付世强 房少军 (Journal of marine science and application, 2008)
A practical antenna has been designed and developed for INMARSAT mobile satellite communications. The design uses low cost materials such as foam and copper foil to create a stacked microstrip antenna array. Several techniques were adopted to enhance the impedance bandwidth and axial ratio bandwidth. The final design parameters were optimized by EM simulation. Finally, the L-strip fed six-element stacked microstrip antenna array was constructed and tested. Simulated and measured results show that in the whole INMARSAT work band, the VSWR of the antenna is less than 1.6, its antenna gain is higher than 15dB and wide-angle axial ratio （AR） 3dB is more than 21°. The antenna has been successfully used with a HNS 9201 terminal.